2002
DOI: 10.1056/nejmoa011033
|View full text |Cite|
|
Sign up to set email alerts
|

Prothrombotic Coagulation Abnormalities Preceding the Hemolytic–Uremic Syndrome

Wayne L. Chandler,
Srdjan Jelacic,
Daniel R. Boster
et al.

Abstract: In the hemolytic-uremic syndrome, thrombin generation (probably due to accelerated thrombogenesis) and inhibition of fibrinolysis precede renal injury and may be the cause of such injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
162
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(176 citation statements)
references
References 27 publications
14
162
0
Order By: Relevance
“…2 The diarrhea-associated hemolytic-uremic syndrome was defined by the presence of the following. 8,9 Prodromal diarrhea, microangiopathic hemolytic anemia, ie a hemoglobin concentration below 10 g per 100 ml and nonimmune hemolysis with fragmented red cells or schistocytes on a peripheral blood smear, increased serum lactate dehydrogenase, reduced serum haptoglobin, thrombocytopenia (a platelet count of less than 150 per nl), and acute renal insufficiency (a reduced glomerular filtration rate less than 30 ml/min per 1.72 m 2 ) without prior history of chronic renal insufficiency. The period of risk for the development of the hemolytic-uremic syndrome was considered to be 14 days after the onset of diarrhea according to data from the literature.…”
Section: Methodsmentioning
confidence: 99%
“…2 The diarrhea-associated hemolytic-uremic syndrome was defined by the presence of the following. 8,9 Prodromal diarrhea, microangiopathic hemolytic anemia, ie a hemoglobin concentration below 10 g per 100 ml and nonimmune hemolysis with fragmented red cells or schistocytes on a peripheral blood smear, increased serum lactate dehydrogenase, reduced serum haptoglobin, thrombocytopenia (a platelet count of less than 150 per nl), and acute renal insufficiency (a reduced glomerular filtration rate less than 30 ml/min per 1.72 m 2 ) without prior history of chronic renal insufficiency. The period of risk for the development of the hemolytic-uremic syndrome was considered to be 14 days after the onset of diarrhea according to data from the literature.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo evidence of coagulation disturbances, i.e., increase in prothrombin fragment 1 ϩ 2, has been found (36) in children who developed HUS upon E. coli O157:H7 infection. Although early studies suggested that fibrinolysis is augmented in Stx-HUS (76), more recent work revealed the presence of higherthan-normal levels of plasminogen-activator inhibitor type 1, indicating that fibrinolysis is substantially inhibited (36).…”
Section: Shiga Toxin or Shiga Toxins?mentioning
confidence: 99%
“…Although early studies suggested that fibrinolysis is augmented in Stx-HUS (76), more recent work revealed the presence of higherthan-normal levels of plasminogen-activator inhibitor type 1, indicating that fibrinolysis is substantially inhibited (36).…”
Section: Shiga Toxin or Shiga Toxins?mentioning
confidence: 99%
“…Dissemination of the toxin from the gastrointestinal tract throughout the bloodstream may be facilitated by binding to leukocytes [40][41][42].Endothelial cells are susceptible to intoxication and may be the most relevant target cells in EHEC-induce HUS. Endothelial cell intoxication is believedto result in increased expression of procoagulants and sub-sequent micro vascular thrombosis [43,44].In addition to Shiga toxins, EHEC,strains (but not -non-EHEC STEC strains ) harbor the locus of enterocytes effacement pathogenicity island and are capable of inducing the attaching and effacing effect .Mutation of gene encoding intimin from an 157:H7 EHEC strain resulted in reduced colonization of neonatal piglets but did not affect neurological complications, which are manifestations of Shiga toxin [45][46][47].STEC infection should be suspected in any patient with grossly bloody diarrhea and should be considered in any individual with diarrhea and cramps. The diagnosis of infection with STEC is vital because of the importance of recognizing potential outbreaks and of taking action to prevent further infections [48 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…E.coli strains that adhere to tissue culture cellsare associated with diarrhea, especially in older children [43].These strains like EAEC are quite heterogonous and perhaps some are more pathogenic than others [44].In addition to E.coli,the genus Escherichia coli contains several other species including Escherichia blattae,Escherichia ferugsonii,and Escherichia vulneris,but these are rarely isolated from human infections.Researchers in Bangladesh reported a strain Hafnia alvei from infants with diarrhea with pathogenic properties similar to those of EPEC.Further DNA studies revealed that these strains although biochemically similar to H.alvei,actually belonged to the genus Escherichia coli and a new species name,Escherichia albertii, was proposed [45,46 ].…”
Section: Pathogenic Ecoli Species Associated With Diarrheamentioning
confidence: 99%